Awareness about Role of Physiotherapy Management During Labour among Obstetricians and Gynacologists (Indian Journal of Public Health Research & Development, 2020)
Background- Pregnancy is the period where a woman goes through many physiological changes, this changesare physical and also emotional. To make this phase comfortable during pregnancy and at labour is importantconcern. Various measures are available for this purpose one of this is physiotherapy. Breathing Exercises,relaxation, swiss ball etc. This study is conducted to find if this is been practised and till what extend andfind the awareness about role of physiotherapy management during labour pain among obstetricians andgynaecologists. This will also help us to overcome the problems. Objectives- To assess the knowledge ofobstetricians about physiotherapy management in labour pain. To determine the awareness about role ofphysiotherapy in managing labour among obstetricians and gynaecologists. Method- total 144 obstetriciansand gynaecologist was taken in this study, they were explained about the purpose of the study. Each of themwas given a self-made questionnaire. Data was recorded. Later statistical analysis was done in accordanceto awareness about physiotherapy management during labour. Result- The present study showed that theawareness among obstetricians in less regarding role of physiotherapy in managing labour due to lack ofknowledge and also due to unavailability of a qualified physiotherapist in that particular area. Conclusion-On the basis of result it can be concluded that there is need for better interaction and communication betweenphysiotherapist and obstetricians and gynaecologists, which can done through journals, seminars, UG/PGcurriculum, social media, workshops.
Keywords: Physiotherapy, labour, awareness, obstetricians, gynaecologist.